A Rare Congenital Anomaly of the Pancreas: A Cadaveric Case Report - Sirasanagandla, Srinivasa Rao; Nayak, Satheesha B; Bhat, Kumar M R (JOP. Journal of the Pancreas, 2013)
Context The pancreas is formed by ventral and dorsal pancreatic buds which arise from the endodermal lining of the gut. When the duodenum rotates to the right, the ventral pancreatic bud migrates dorsally and finally come and lie below the dorsal pancreatic bud. The developmental errors in the rotation of these components lead to annular pancreas. Case report We report a rare type of the incomplete annular pancreas around the contents of right free margin of lesser omentum. There was an extra pancreatic mass situated horizontally immediately above the superior border of the pancreas, situated behind the lesser omentum. The right end of this mass extended into the epiploic foramen and incompletely encircled the portal vein, bile duct and hepatic artery proper from behind. The left end of the extra pancreatic mass was extended towards the lesser curvature of the stomach. Further, this mass completely surrounded the origin of three branches of the celiac trunk. Its right end was found to be continuous with the head of the pancreas, close to the pylorus. Histology of the extra pancreatic mass revealed the presence of normal pancreatic tissue. Conclusion preoperative diagnosis of this rare anomaly is of clinical importance during surgeries involving the contents of right free margin of lesser omentum and epiploic foramen. Image: Accessory pancreatic mass above the superior border of the body of pancreas.